Genomic Analysis of Bacterial Isolates from Guinea Pigs (Cavia porcellus) and Brown-Throated Sloths (Bradypus variegatus) - Carhuaricra Huaman, Dennis Edgardo (2023)
Genomics has revolutionized our understanding of the microbial world. From the surveillance and epidemiology of emerging pathogens to comprehending the evolution and adaptation of bacteria to their hosts. Despite enormous advances, significant gaps persist, particularly in the study of the diversity and evolution of bacteria residing in wildlife microbiomes and the emergence of bacterial pathogens affecting livestock in low- and middle-income countries. In the present work, using different comparative genomics approaches, I study three bacterial species: the pathogenic Salmonella Typhimurium isolated from guinea pig (Cavia porcellus) in Peru and Kerstersia gyiorum and Neisseria sp. isolated from free-living brown-throated sloths (Bradypus variegatus) in Brazil. Salmonella Typhimurium is the main pathogen infecting guinea pigs in Peru. First, I perform a genomic characterization of S. Typhimurium infecting guinea pigs in Lima-Peru describing the presence of two ST19 clusters, one of them being a monophasic variant carrying the plasmid of virulence (pLST) and genetically related to human isolates. Second, using a larger genomic data collection from South America and time-scaled phylogenetic analysis I describe the emergence of a Peruvian lineage of S. Typhimurium (B6 lineage) associated with guinea pigs and humans. The emergence of this highly prevalent lineage in Peruvian guinea pigs coincides with the recent intensification of guinea pig production and exhibits genetic signals of host adaptation with multiple loss-of-function mutations in genes encoding for structures involved in host-cell interaction and host specificity. These results highlight the risks of intensive livestock production in pathogen emergence. The genomic analysis of brown-throated sloth isolates was performed. First, K. gyiorum exhibited phylogenetic and gene content variation structured according to the host. Additionally, differences in GC content, genome size, differential presence of mobile genetic elements (plasmid and phages) and defense systems suggest that K. gyiorum populations have followed divergent evolutionary trajectories that led to the establishment of host-restricted lineages. The presence of genes with different functions may be important for the adaptation of K. gyiorum to different niches. Second, a new species of Neisseria, named Neisseria bradyp is characterized genomically, which represents the first known species associated with common sloths. Average Nucleotide Identity (ANI) and phylogenomics analyses within the Neisseria genus revealed that N. bradyp is genetically distinct from other 32 Neisseria species. Additionally, N. bradyp exhibited exclusive genetic content that is notably enriched in carbohydrate metabolism and other pathways. Furthermore, it displayed differences in its capsular structure, which may play a significant role in host colonization. The results of this work highlight the importance of genomics data and bioinformatics tools to study the emergence of novel pathogenic variants and disentangle the evolution and host adaptation of bacteria to their host.